История России: энцикл. / А. В. Голубев, В. Л. Телицын, Т. В. Черникова - Голубев Александр Владимирович (Росмэн, 2009)
Экземпляры: ф. 1 (20100412) / Инвентарный номер: 95998 / Цена: 146.00 / Авт.знак: Г 62 / ББК: 63.3(2)я2